Characterizationof Hydraulic Suspension System, on The Basis of Accumulator Pressure Values for a Special Purpose Vehicle. (2017) - Ansari, Faisal Ahmed; Ranjan, R.; Korade, D.N.; Jagtap, K.R.
Abstract: This paper presents the characterization of the hydraulic suspension system of Special Purpose Trailer which is a modular semi-trailer used for carrying heavy commercial equipment's and heavy cargos. Presently automotive industry is using the knuckle joint hydraulic suspension system for the above mentioned trailer. The study includes the characterization of the hydraulic spring of the system based on the polytropic process and mathematical modelling of the quarter car hydraulic suspension system in MATLAB/SIMULINK. Basically the hydraulic suspension system consists of a hydraulic cylinder ram, pressurized hydraulic circuit, cut off valves, accumulator, and axel-wheel assembly. The study mainly concentrates on the accumulator pressure values as changing the pressure of accumulator directly affects the behavior of suspension system. MATLAB/SIMULINK software is used for obtaining the behavioral pattern of the suspension system on account of different accumulator pressure values. And finally the best possible value of accumulator pressure is obtained under the working conditions of the trailer.